Phylogenomics enables biogeographic analysis and a new subtribal classification of Andropogoneae (Poaceae—Panicoideae). Issue 6 (17th December 2020) - Welker, Cassiano A. D.; McKain, Michael R.; Estep, Matt C.; Pasquet, Rémy S.; Chipabika, Gilson; Pallangyo, Beatrice; Kellogg, Elizabeth A.
Abstract: The grass tribe Andropogoneae (Poaceae—Panicoideae) includes several important crops such as maize, sugarcane, and sorghum, and dominates the tropical grasslands of the world. We present here a plastome phylogeny of the tribe with the largest sample of genera to date (about 73%), including 65 newly assembled plastomes, together with a broad biogeographic analysis of Andropogoneae. Major relationships found in previous phylogenetic studies were confirmed here, with most nodes having higher resolution and support, including those of the backbone of the tree, which had been a major problem in previous phylogenies of the tribe. Our dated tree suggests that Andropogoneae diverged from Arundinelleae in the Early Miocene, while the "core Andropogoneae" clade originated in the Late Miocene. The tribe originated in East Asia, but intercontinental dispersal has been common, with many independent dispersal events to Africa and the New World. Based on the plastome phylogeny, we propose here a new classification of Andropogoneae as most of its previously accepted subtribes are not monophyletic. Our classification comprises 14 subtribes, 92 genera, and ∼1224 species. About 90% of the Andropogoneae species could be assigned to a subtribe, which represents a major step toward clarification of the taxonomy of the tribe. The remaining taxa were placed incertae sedis pending additional molecular data. The new subtribes Chrysopogoninae and Rhytachninae are described herein. Our plastome trees also indicate that several Andropogoneae genera are para‐ or polyphyletic and require additional studies to define their circumscriptions. Abstract : A plastome phylogeny of Andropogoneae (Poaceae) is presented with the largest sample of the tribe to date. Andropogoneae likely originated in East Asia, but intercontinental dispersal has been common, with many independent dispersal events to Africa and the New World. A new subtribal classification of Andropogoneae is proposed, including 14 subtribes, 92 genera, and ∼1224 species.